2018
DOI: 10.1096/fj.201800200r
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular β‐amyloid deposition and associated microhemorrhages in a Tg2576 Alzheimer mouse model are reduced with a DHA‐enriched diet

Abstract: Cerebral amyloid angiopathy (CAA) is a major contributor to Alzheimer's disease (AD) pathogenesis. Like AD, CAA is often accompanied by marked inflammation, aggravating associated vasculopathies. No evidence-based prevention or treatment strategies are available. Here, we evaluate the possible beneficial effect of a diet enriched with docosahexaenoic acid (DHA), which is known to attenuate inflammation in CAA. Tg2576 mice, a transgenic model of AD/CAA, were fed a DHA-enriched diet starting at 2 mo of age and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…On an organ level, metabolites control pathophysiological reactions such as asthma via leukotrienes 121 . In complex organisms, nutritional interventions such as supplementation of omega-3 fatty acids proved to have multiple benefits, while lacking severe side effects 122,123 , and a plethora of studies has analyzed the phenotypic modulations evoked by feeding various supplemented diets to model organisms of ageing-associated diseases 124126…”
Section: Discovering Active Metabolitesmentioning
confidence: 99%
“…On an organ level, metabolites control pathophysiological reactions such as asthma via leukotrienes 121 . In complex organisms, nutritional interventions such as supplementation of omega-3 fatty acids proved to have multiple benefits, while lacking severe side effects 122,123 , and a plethora of studies has analyzed the phenotypic modulations evoked by feeding various supplemented diets to model organisms of ageing-associated diseases 124126…”
Section: Discovering Active Metabolitesmentioning
confidence: 99%
“…The impact of 12/15-LOX is not limited to the peripheral nervous system, but also appears to play a strong role in the development of several central nervous system diseases. Interestingly, the 12/15-LOX pathway has been recently implicated in Alzheimer's disease (Hur et al, 2018;Pratico et al, 2004;Lebeau et al, 2001;Lebeau et al, 2004). There is also compelling data for the involvement of 12/15-LOX in brain damage due to stroke (Jin et al, 2008;Liu et al, 2017;van Leyen et al, 2006;van Leyen et al, 2014;Yigitkanli et al, 2013;Yigitkanliet al, 2017).…”
Section: Diabetic Peripheral Neuropathy and Other Central Nervous Sysmentioning
confidence: 99%
“…Several in vivo studies in APP transgenic mice have shown that the supplementation of docosahexaenoic acid (DHA, 22:6), an ω-3 fatty acid rich in the brain, ameliorates cognitive dysfunction [13, 14, 15], Aß pathology [1314, 1623], or tau pathology [15, 18, 24]. It has also been reported that DHA inhibits in vitro Aß aggregation [25, 26], Aß production [16, 22, 2729], or Aß toxicity in SH-SY5Y cells [26], primary neurons [30] or induced pluripotent stem cells derived from AD patients [31].…”
Section: Introductionmentioning
confidence: 99%